Impact of immigration background on feasibility of electronic patient-reported outcomes in advanced urothelial cancer patients - Ozan Yurdakul; Abdulkarim Alan; Johanna Krauter; Stephan Korn; Kilian Gust; Shahrokh F. Shariat; Melanie R. Hassler (Health and Quality of Life Outcomes)
Abstract Background Electronic patient-reported outcomes (ePROs) have been shown to enhance healthcare quality by improving patient symptom management or quality of life (QoL). However, ePROs data for urothelial cancer (UC) patients receiving systemic therapies are scarce, and the application of ePROs in this patient cohort may need specific setups. This study tested the feasibility of ePROs for UC patients receiving systemic therapies in the outpatient clinic of a tertiary care center. Patients and Methods From January 2022 to April 2023, 30 UC patients receiving systemic cancer therapies received ePROs based on the Common Terminology Criteria for Adverse Events (CTCAE) and European Organization for Research and Treatment of Cancer Core Quality of Life questionnaires (EORTC QLQ-30) to report their symptoms and QoL during systemic therapy, in total, 125 questions for every therapy cycle. The proportion of patients adherent to the ePROs was assessed to evaluate feasibility, with a preset threshold of 50%. At least half of all treatment cycles with a minimum of two consecutive ePROs (corresponding to two successive therapy cycles) had to be completed to be counted as adherent, and a maximum of six successive therapy cycles was followed by ePROs. Descriptive statistics were calculated for clinical and demographic patient characteristics. T-test and chi-square-test analyses were performed to study the association between ePROs adherence and clinical or demographic factors. The digital process was closely monitored for procedural impediments that could occur. Results 21 (70%) of the included 30 patients adhered to the provided ePROs, significantly higher than the predetermined threshold of 50%. Adherence remained above 70% until the end of the observation period. A significant negative effect of immigration background on ePROs compliance was observed (p = 0.006). No other variables were significantly associated with ePROs compliance. Conclusions In this study, ePROs were a feasible method to assess symptoms and QoL during the systemic cancer therapy of UC patients at our center. The compliance of patients with immigration backgrounds was the most significant barrier to using ePROs in this setting. However, the study is limited by the exclusion of patients without email access and the lack of assessment of physician compliance with the ePROs data, which may affect the generalizability and implementation of the findings.